KOMBINASI PAKAN TWO PHASE PROTEIN DENGAN ASAM SITRAT SEBAGAI ACIDIFIER TERHADAP MASSA KALSIUM DAN PERTUMBUHAN TULANG AYAM BROILER - Dameria M Panjaitan; N. Suthama; U. Atmomarsono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
The aim of the research was to determine bone calcium mass and growth rate of broiler chicken fed two phase dietary protein combined with citric acid as acidifier. Experimental animals were 168 broilers (84 males+84 females) MB 202strains of 7 days old with an average body weight of 186.23 ± 0.68 g. Research was arranged in a completely randomized design (CRD) with 7 treatments and 4 replications (6 birds each). The treatments were: P0 = control diet (without phase dietary protein and citric acid); P1 = two phase dietary protein without citric acid; P2 = two phase dietary protein + 0.8% citric acid of lime; P3 = two phase dietary protein + 0.4% citric acid synthetic; P4 = two phase dietary protein + 0.8% synthetic citric acid; P5 = two phase dietary protein + 1.2% synthetic citric acid; and P6 = two phase dietary protein + 1.6% synthetic citric acid. The parameters measured in the present research were bone calcium mass and growth rate (weight, length, and strength) of tibia and metatarsus of broiler chicken. The data were subjected to analysis of variance by F test followed by Duncan test (P<0.05). The results showed that two phase dietary protein combined with citric acid significantly (P<0.05) increased weight, length, and strength of tibia and metatarsus, and bone calcium mass. The conclusion is that feeding two phase dietary protein combined with citric acid as acidifier with level of 0.4-1.6% was able to increase growth rate (weight and length), calcium mass, and strength of bone in broiler chicken.